Studi Eksperimen Pengaruh Kecepatan Aliran terhadap Performa Double Pipe Heat Exchanger - Elby , Alvin Christian ; Amalia, Rif?ah ; Safitra, Arrad Ghani (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
Heat Exchanger is a device used to transfer thermal energy between two or more fluids, or between solid surface and fluids, with different temperature. One of low capacity heat exchanger known in Industry is the double pipe heat exchanger. This heat exchanger usually consists of two concentric pipes with plain of finned inner pipe. Because of its low capacity, the performance of double pipe heat exchanger needs to be improved to achieve optimal operating condition. This research contains an experimental study of optimizing double pipe heat exchanger?s performance by varying the Reynolds number which is reviewed from the value of Nusselt number (Nu) and friction factor (f). The double pipe heat exchanger is tested with 2500, 3500, 4500, 5500, and 6500 Reynolds number value with 20?C of cold fluid flows through the inner pipe, and 40?C of hot fluid flows through the annulus pipe. The fluids flow with counterflow condition. Based from the experimental results, it is known that by the increasing of Reynolds number, the Nusselt number increased by 2.14 times, and the friction factor decreased by 1.13 times from Reynolds number of 2500 to Reynolds number of 6500. The optimal Reynolds number resulted in Reynolds number of 3900 with Nusselt number of 32.41 and friction factor of 0.0491.